Multinationals and structural transformation - Vanessa Alviarez; Cheng Chen; Nitya Pandalai-Nayar; Liliana Varela; Kei-mu Yi; Hongyong Zhang (Inter-American Development Bank (IDB), 2023)
We study the role of multinationals (MNCs) in facilitating firm-level and aggregate structural transformation. Using a stylized model of multinational production and trade, we show that an inward multinational liberalization in the manufacturing sector raises employment in host country firms, and decreases manufacturing employment, while also raising services employment, in the parent firms. We also show the conditions under which aggregate structural transformation occurs. We test the model's firm-level predictions by using confidential microdata from Japan. We study the response of Japanese MNC parents and their affiliates in China to an exogenous change in China's openness to foreign direct investment (FDI). We find that in industries where inward FDI was encouraged, Japan MNC's affiliates in China experienced increases in their employment. We also find that MNC parents in the encouraged industries experienced decreases in home country manufacturing employment and increases in home country services and R&D employment. Finally, using microdata for several advanced and middle-income countries, we decompose the change in overall manufacturing employment shares into MNC and non-MNC components. We find a significant role for MNCs across all countries, suggesting the mechanism we highlight is an important global driver of structural transformation.
Keywords: F41; F44; 330; Multinational firms; Structural transformation; Manufacturingemployment